The Impact of Oil Revenues on the Iranian Economy and the Gulf States - Christian Dreger; Teymur Rahmani (Institute for the Study of Labor (IZA), 2014)
In line with the neoclassical growth model a persistent stream of oil revenues might have a long lasting impact on GDP per capita in oil exporting countries through higher investment activities. This relationship is explored for Iran and the countries of the Gulf Cooperation Council (GCC) using (panel) cointegration techniques. The existence of cointegration between oil revenues, GDP and investment can be confirmed for all countries. While the cointegration vector is found to be unique for Iran, long run equations for GDP and investment per capita are distinguished for the Gulf countries. Both variables respond to deviations from the steady state, while oil income can be treated as weakly exogenous. The long run oil elasticities for the Gulf states exceed their Iranian counterparts. In addition, investment in Iran does not react to oil revenues in the long run. Hence, oil revenues may have been spent less wisely in Iran over the past decades.
Keywords: F43; O53; Q30; C33; 330; oil exporting countries; oil revenues; panel cointegration